Determining the tuning and matching requirements of RF coils using electromagnetic simulation and electric circuit analysis - Cassidy, P; Clarke, K; Edwards, D (2005)
Electromagnetic simulation using the transmission-line modelling method in conjunction with electric circuit analysis is applied to extract the tuning and matching requirements of RF coils for magnetic resonance imaging. Free-ringing microimaging RF coils were modelled in the unloaded and Krebs-Henseleit physiological buffer solution loaded condition. The simulations determined the frequency response and equivalent lumped-element circuit components of resistance, inductance, (fixed) capacitance, and coupling coefficient. Equivalent lumped-element electric circuit representations were derived for RF coils, and circuit analysis was applied to determine the tuning and matching requirements for the desired resonance frequency and characteristic impedance, respectively. Both capacitive and inductive matching schemes were considered. Experimental comparisons were performed with an agreement of less than 3 pF for the (variable) tuning and matching capacitances used in the tuning and matching networks, thus enabling component selection and validation of the methods. © 2005 Wiley Periodicals, Inc.